2014
DOI: 10.1155/2014/470253
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer Stem Cell Lose Their Stemness Default State after Exposure to Microgravity

Abstract: Microgravity influences cell differentiation by modifying the morphogenetic field in which stem cells are embedded. Preliminary data showed indeed that stem cells are committed to selective differentiation when exposed to real or simulated microgravity. Our study provides evidence that a similar event occurs when cancer stem cells (CSCs) are cultured in microgravity. In the same time, a significant increase in apoptosis was recorded: those data point out that microgravity rescues CSCs from their relative quies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 34 publications
3
40
0
Order By: Relevance
“…The ultimate evidence that cancer cells lose their malignancy under microgravity is still missing, but there are some clues in this direction. Lung cancer stem cells have been observed to lose their stemness under microgravity, downregulating Oct-4 and Nanog expression 29 . Thyroid cancer cells have shown higher production of antiproliferative and antimetastatic factors 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate evidence that cancer cells lose their malignancy under microgravity is still missing, but there are some clues in this direction. Lung cancer stem cells have been observed to lose their stemness under microgravity, downregulating Oct-4 and Nanog expression 29 . Thyroid cancer cells have shown higher production of antiproliferative and antimetastatic factors 30 .…”
Section: Discussionmentioning
confidence: 99%
“…It has since become clear that system level changes occur in microgravity fields (Crawford‐Young, ). More specifically, microgravity has been shown to affect cell morphology (Crawford‐Young, ; Testa et al., ), cytoskeletal organization (Masiello et al., ), early development (reviewed by Ogneva, ; see also Dournon, ), the likelihood of the open state of ion channels (Goldermann & Hanke, ), gene expression profiles (Pardo et al., ), differentiation (Pisanu et al., ), and apoptosis (Monici et al., ). Microgravity, in most cases so far, has been shown to be an inhibitor of tissue growth and regeneration in mammalian tissues (Blaber et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In cervical cancer, ALDH1-positive cells, like other solid tumors, are known to be more tumorigenic than negative ones, and we used ALDH1 as a marker of cervical CSCs (25)(26)(27)(28)(29)(30)(31)(32)(33)(34). First, using the cervical cancer cell line CaSki we confirmed that the expression of PAI-1 was significantly increased by changing coatings of culture plates as described (35), especially collagen IV-coating, confirmed by enzyme-linked immunosorbent assay (ELISA).…”
Section: Introductionmentioning
confidence: 99%